VOCATIONAL SCHOOL STUDENTS' LANGUAGE LEARNINGSTRATEGIES AND ENGLISH PROFICIENCY AS INDICATED BY (A Correlative Study on Third Grade Students of Business and Tourism Vocational I THEIR TOEIC SCORES School in SMK Negeri 3 Bandung) - Lismawatti Emma Neneng, - (2007)
The main objectives of this study were likely to have a better understanding of how the students learn English language in vocational school, to describe their English proficiency as indicated by TOEIC scores and to find out the correlation between their strategies and English proficiency. The study used descriptive method with quantitative and qualitative data. The data were acquired from questionnaire, interview, and documentary analysis format. The questionnaire of Strategy Inventory for Language Leaming (SILL) version 7. 0 ( Oxford, 1990 :293) was modified and translated into Indonesian language. Semi structured interview toward the students as well as the teacher was applied to verify the students' responses in the questionnaire. Documentary analysis format was employed to get the information about students' English proficiency. The samples were 135 third grade students of Business and Tourism Vocational School in SMK Negeri 3 Bandung. The major findings revealed that the students' frequency in using language learning strategies were moderately intensive (mean 2.85) with metacognitive strategies as the most frequently used (mean 3.13) and social strategies as the least employed (mean 2.62). Further, their English proficiency as indicated by TOEIC scores was categorized into Novice level (mean 250). Using Pearson's product rnoment correlation, the study indicated that there was a positive significant correlation between language learning strategies and students' English proficiency (r=0.173, p=0.022) In conclusion, students employed various language learning strategies in learning English to improve their proficiency. Therefore, they give the teachers valuable clues about how their students learn English language and thus, teacher could improve their teaching. The low correlation value found in this study was indicated by the low of students' motivation as revealed in the interviews. Accordingly, further research need to be tested.